2018
DOI: 10.1111/pedi.12778
|View full text |Cite
|
Sign up to set email alerts
|

Using simple clinical measures to predict insulin resistance or hyperglycemia in girls with polycystic ovarian syndrome

Abstract: Background: Polycystic ovarian syndrome (PCOS) includes insulin resistance (IR) and impaired glucose tolerance (IGT) in youth, and a greatly elevated risk of type 2 diabetes in adulthood. Identifying IR is challenging and documenting IGT requires an oral glucose tolerance test (OGTT). Objective: Identify an easily applied surrogate measures for IR and IGT in girls with PCOS. Methods: We studied 28 girls with PCOS [BMI percentile 98 (83,99); 15.5 (14.5,16.6) years of age] and 20 with normal menses [BMI percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
(125 reference statements)
1
11
0
Order By: Relevance
“…The prevalence of impaired glucose tolerance (IGT) was 25% in a Chinese study of 20 overweight or obese girls with PCOS and 24% in a larger Canadian study of 117 girls of similar weight 16,17 . In a mixed BMI cohort of 28 girls with PCOS of similar racial/ethnic composition as our study, 32% had IGT 27 . These rates of dysglycemia are nearly twice that reported for adolescent girls 13.4% (10.8–16.5) included in a recent NHANES study 28 .…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…The prevalence of impaired glucose tolerance (IGT) was 25% in a Chinese study of 20 overweight or obese girls with PCOS and 24% in a larger Canadian study of 117 girls of similar weight 16,17 . In a mixed BMI cohort of 28 girls with PCOS of similar racial/ethnic composition as our study, 32% had IGT 27 . These rates of dysglycemia are nearly twice that reported for adolescent girls 13.4% (10.8–16.5) included in a recent NHANES study 28 .…”
Section: Discussionmentioning
confidence: 42%
“…16,17 In a mixed BMI cohort of 28 girls with PCOS of similar racial/ethnic composition as our study, 32% had IGT. 27 These rates of dysglycemia are nearly twice that reported for adolescent girls 13.4% (10.8-16.5) included in a recent NHANES study. 28 Our rates of pre-diabetes showed that early evidence of dysglycemia was common at 24%, similar to other adolescent PCOS cohorts and is related to T2D development.…”
Section: Resultsmentioning
confidence: 81%
“…Therefore, PCOS patients are prone to have diabetes during pregnancy. 22,23 According to another study, high androgen levels in PCOS patients cause increased secretion of vascular smooth muscle cells, resulting in narrowing of the vascular lumen, increased blood flow resistance, poor vascular endothelial function, and eventually the development of pregnancy-induced hypertension. 24 In this study, compared with patients in group B, the incidence of gestational diabetes and hypertension in pregnancy in group A was significantly lower, which may be due to the low serum AMH level.…”
Section: Groupsmentioning
confidence: 99%
“…Similarly, the intravenous glucose tolerance test (IVGTT) is non-physiological due to the IV infusion that bypasses the gut [ 21 ]. Several surrogate indices, including HOMA [ 22 ], QUICKI [ 23 ], and the Matsuda index [ 24 ] have been developed to efficiently quantify in the clinical setting [ 23 , [25] , [26] , [27] , [28] , [29] ]. Alternatively, the Oral Minimal Model (OMM), a mathematical model of glucose-insulin dynamics in the more physiological conditions of an oral glucose tolerance test (OGTT) [ [30] , [31] , [32] ], may be used to estimate .…”
Section: Introductionmentioning
confidence: 99%